Peningkatan Kinerja Guru dalam Melaksanakan Pembelajaran yang Efektif Melalui Supervisi Observasi Kelas di SD Negeri 3 Sekongkang Tahun Pelajaran 2020/2021 - Muhiddah (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2021)
The purpose of this school action research is to determine the extent to which the improvement of teacher performance in implementing effective learning at SD Negeri 3 Sekongkang through classroom observation supervision. In this school action research, the variables to be studied were improving teacher performance through coaching classroom observation supervision at SD Negeri 3 Sekongkang, Sekongkang District, West Sumbawa Regency with data collection techniques, namely observation and questionnaires. This action research was conducted in 3 cycles, from the results of the actions taken were proven to improve teacher performance by achieving ideal standards. improving teacher performance in implementing effective learning, through coaching supervision of classroom observations, the results are very good. This can be seen at the first meeting of the 5 teachers who were at the time of this research that the average score reached; 60.7% increased to 71.4% and in cycle 3 increased to 82.1%. The results of this school action research indicate that the application of the principal's classroom observation supervision can improve teacher performance by reaching 100% completeness, the teacher's response is very positive to the coaching carried out by the principal through classroom observation supervision.